Faces of Republican Turkey: Beyond the Modernization Hypothesis - Suda, Emine Zeynep; Uslu, Ates; Korkmaz, Emre Eren (Istanbul University Press, 2020)
Methodologies and problématiques in social sciences and humanities are closely linked with the dominant ideologies in which they are produced, which, in turn, are deeply embedded in a specific social and economic formation. Thus, it is not a coincidence if, throughout the twentieth century, Turkish politics and society have been frequently analyzed through the lens of modernization. Generations of thinkers, politicians, social scientists, and historians have asked questions related to a presupposed transition from traditional to modern society in Turkey. Some of them supposed that the transition took place in the early republican period, in the 1920s and 30s, in an abrupt way, while it was a smooth, lengthy process, spanning from the late 18th to the late 20th century. Those idealizing the modernization and exaltating the modernizers were confronted by critiques of modernity; while the former camp was a heterogenous mixture of various political and historiographic tendencies, the latter was also far from being homogenous, and included both traditionist and post-modernist critical voices towards modernity. While differences of opinion and methodology within and between the modernist and anti-modernist tendencies are striking, there are also common denominators uniting them in a single narrative. According to this narrative, modernity consists of a set of references allegedly developed in Western Europe: Women's emancipation, bureaucratization of state apparatus, development of literacy and creation of a new education system, secularization in political references, anticlerical politics, transition towards a representative democracy, and many other developments are considered within a single, unitary process of (Western) development. Whig historians, Hegelian philosophers, and positivist thinkers praised this supposedly combined development as the March of Intellect, and late-19th century vitalism, culminating in the works of Friedrich Nietzsche, condemned it as a unitary process of decadence of humanity. Both pro- and anti-modernist approaches to the 20th-century politics and society in Turkey are heir to these broader pro- and anti-modernist theories. Through this scope, the foundation of the Turkish Republic was praised or criticized as the culmination of a modernization process launched by a conscious, Westernizing elite. The modernization literature, despite its considerable contribution to the understanding of modern Turkish politics and society, suffers from striking shortcomings. As a teleological approach, it transforms specific historical events and tendencies into the moments of one single line of development towards modernization: Electoral reforms, administrative centralization, or the rise of the printing press are taken as the examples of a grand march towards modernity, or as the symptoms of a belated involvement in modernization. As an opinionated approach, the modernization literature takes for granted a series of debatable assertions: The bureaucratic circles of the late Ottoman and early republican Turkey are conceived of as independent social and political actors, and the republican state is placed in continuity with an allegedly all-powerful Ottoman state apparatus. The present volume, Faces of Republican Turkey, is an attempt at presenting an alternative reading of Turkey's twentieth-century politics. Rather than drawing on an elite-based study of Turkish politics, it examines the interplay between the variety of social actors, and their relationship with political power. Avoiding a homogenizing look towards society, it focuses on the analysis of gender and property relations within the society, and emphasizes the embeddedness of political thought and institutions in the social dynamics. The contributors use a wide range of critical methodologies, including, amongst others, historical materialism, social reproduction theory, social and political memory analysis, discourse analysis, and Frankfurt School critical theory. Each contribution is expected to focus on a topic related to Turkish politics and society. The authors present a critical account of the modernity and modernization-centered literature on the selected topic, and develop alternative approaches through the analysis of a specific case, using qualitative and historical research methodologies.